2020
DOI: 10.3390/cells9030692
|View full text |Cite
|
Sign up to set email alerts
|

NANOG/NANOGP8 Localizes at the Centrosome and is Spatiotemporally Associated with Centriole Maturation

Abstract: NANOG is a transcription factor involved in the regulation of pluripotency and stemness. The functional paralog of NANOG, NANOGP8, differs from NANOG in only three amino acids and exhibits similar reprogramming activity. Given the transcriptional regulatory role played by NANOG, the nuclear localization of NANOG/NANOGP8 has primarily been considered to date. In this study, we investigated the intriguing extranuclear localization of NANOG and demonstrated that a substantial pool of NANOG/NANOGP8 is localized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“… 22 Recently, cytoplasmic, more precisely centrosome localization of Nanog, during the cell cycle was detected in various tumor and non-tumor cell types. 23 Fan et al, 2021 24 recently described a fibrocartilage stem cell population in a fibrous superficial zone of the adult human mandibular condyle. The formation of these cells occurs during the late period of the embryonic stage, 25 which corroborate with our data.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Recently, cytoplasmic, more precisely centrosome localization of Nanog, during the cell cycle was detected in various tumor and non-tumor cell types. 23 Fan et al, 2021 24 recently described a fibrocartilage stem cell population in a fibrous superficial zone of the adult human mandibular condyle. The formation of these cells occurs during the late period of the embryonic stage, 25 which corroborate with our data.…”
Section: Discussionmentioning
confidence: 99%
“…The functional paralog of Nanog, NanogP8, differs from Nanog in only three amino acids and exhibits similar reprogramming activity. E. Mikulenkova et al investigated the intriguing extranuclear localization of Nanog and demonstrated that a substantial pool of Nanog/NanogP8 is localized at the centrosome [31]. NanogP8 is the main regulator of gastric cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mikulenkova, together with the paper’s co-authors, found that the nuclear protein NANOG/NANOGP8 is localized in the centrosome [ 2 ]. The above examples show that various regulatory pathways intersect in the centrosome; thus, regulatory proteins are concentrated in the centrosome.…”
mentioning
confidence: 99%